Improving oral communicative competence in English using project-based learning activities - Abu Bakar, Noor Idayu; Noordin, Nooreen; Mohamed Razali, Abu Bakar (https://doi.org/10.5539/elt.v12n4p73, 2019)
The quasi-experimental study investigated the effectiveness of using project-based learning (PjBL) activities as a teaching strategy in improving the oral communicative competence of Malaysian English language learners. The participants included 44 diploma students enrolled in a Communicative English course at a technical college in the Peninsular Malaysia, who were purposely selected for the study. The intervention comprised a 12-week lessons taught using PjBL teaching strategy and centred on eight PjBL activities. Data were collected using a speaking test and a listening test, which were administered as pre-tests and post-tests, and a student questionnaire which was administered at the end of the study. Data analysis involved the procedure of MANOVA, as well as descriptive statistics such as mean, standard deviation and percentage. The findings revealed a significant improvement in the learners’ overall oral communicative competence and a high perception of PjBL by the learners. It is concluded that PjBL teaching strategy is effective in improving the oral communicative competence of the English language learners. The study recommends the use of PjBL as a suitable English language teaching strategy for technical students who are generally low proficient English language learners.